Can mobile phone-based household surveys in rural Papua New Guinea generate information representative of the population surveyed? - Benson, Todd (International Food Policy Research Institute, 2019)
Conducting household surveys through face-to-face interviewing in rural Papua New Guinea is beset with difficulties and high costs. With phone network coverage spreading across PNG, using mobile phones to obtain information from respondents can allow such surveys to be done more quickly and at significantly lower cost. However, not all rural households own mobile phones. In this Project Note, an assessment is made of whether survey information collected by calling respondents on their mobile phones will be representative of the population surveyed or, rather, might be subject to systematic biases. This assessment is done by analyzing the characteristics of households in four rural areas of PNG that were interviewed in a field survey in mid-2018.